Perception of fear and coercive management of victims of intercity bus robberies - Machado, Eduardo Paes (Criminology & criminal justice, 2017)
Drawing on interviews with drivers and passengers, this article discusses the perception of fear and management of victims of intercity bus robberies. It compares the victimization that takes place during bus robberies on highways and where buses are diverted off route. It addresses the relationship between perception of fear, the vehicle characteristics, multiplicity of victims, and duration of robbery. The article highlights important variations in the perception of violence according to the robbers’ victim management style as well as to the roles of and responses by drivers and passengers in the different phases of the coercive process. It concludes by arguing that it is urgent for the state to exercise its regulatory authority over these crimes and to guarantee security in bus transport.